NUPR1 interacts with eIF2α and is required for resolution of the ER stress response in pancreatic tissue. (25th January 2021) - Borrello, Maria Teresa; Santofimia‐Castaño, Patricia; Bocchio, Marco; Listi, Angela; Fraunhoffer, Nicolas; Soubeyran, Philippe; Chevet, Eric; Pin, Christopher; Iovanna, Juan
Abstract : Nuclear protein 1 (NUPR1) is a stress response protein overexpressed upon cell injury in virtually all organs including the exocrine pancreas. Despite NUPR1's well‐established role in the response to cell stress, the molecular and structural machineries triggered by NUPR1 activation remain largely debated. In this study, we uncover a new role for NUPR1, participating in the unfolded protein response (UPR) and the integrated stress response. Biochemical results and ultrastructural morphological observations revealed alterations in the UPR of acinar cells of germline‐deleted NUPR1 murine models, consistent with the inability to restore general protein synthesis after stress induction. Bioinformatic analysis of NUPR1‐interacting partners showed significant enrichment in translation initiation factors, including eukaryotic initiation factor (eIF) 2α. Co‐immunoprecipitation and proximity ligation assays confirmed the interaction between NUPR1 and eIF2α and its phosphorylated form (p‐eIF2α). Furthermore, our data suggest loss of NUPR1 in cells results in maintained eIF2α phosphorylation and evaluation of nascent proteins by click chemistry revealed that NUPR1‐depleted PANC‐1 cells displayed a slower poststress protein synthesis recovery when compared to wild‐type. Combined, these data propose a novel role for NUPR1 in the integrated stress response pathway, at least partially through promoting efficient PERK branch activity and resolution through a unique interaction with eIF2α. Abstract : Upon induction of ER stress, NUPR1 is expressed and interacts with eIF2α and p‐eIF2α. In pancreatic tissue this interaction is required for relieving stress. In the absence of NUPR1, the transcriptional and translational blocks promoted by p‐eIF2α are mantained and a global reduction of UPR regulators expression is reported.